Data Recovery from Ransom ware Affected Android Phone using Forensic Tools - Rughani, ph (International Journal of Computer Sciences and Engineering, 2025)
With increasing use of computers and mobile phones, malware attacks are also increased in last few years. Ransomware – one of the malware has become the biggest challenge for security experts and end users. There is urgent need to defend computers and smartphones against possible ransomware attacks. However, it may not be possible to stop such attacks, the attempt can be made to recover from such attacks. This paper discusses possibilities to recover data from encrypted files from ransomware affected android phones. The work presented in this paper was carried out to assist forensic investigators and assure end users that there are possible ways to retrieve their data without paying ransom money. It would be encouraging for end users to know that in most of the cases the data encrypted by a ransomware can be retrieved with help of forensic tools and it will be equally discouraging for attackers. The paper is focused on data recovery from ransomware affected android phones.